2021
DOI: 10.1097/md.0000000000025635
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of metastasis and survival between extrahepatic and intrahepatic cholangiocarcinoma

Abstract: To date, extrahepatic cholangiocarcinoma (ECCA) and intrahepatic cholangiocarcinoma (ICCA) have rarely been compared; therefore, we attempted to learn more about the rates of metastasis and survival in both ICCA and ECCA. Data of patients in the SEER database diagnosed with ICCA or ECCA were extracted to analyse the rate of metastasis and survival. Univariate and multivariate logistic regression analyses were performed to identify the risk factors for metastasis. Propensity score matching (PSM) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
(23 reference statements)
0
14
0
Order By: Relevance
“…ICC is the second most common primary malignancy of the liver following hepatocellular carcinoma [8]. DM occurs in ICC patients, OS falls sharply and the incidence of distant metastases from intrahepatic cholangiocarcinoma is about 40% [4]. Due to its low prevalence, there are few large-scale studies for clinical guidance and management of patients with ICC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ICC is the second most common primary malignancy of the liver following hepatocellular carcinoma [8]. DM occurs in ICC patients, OS falls sharply and the incidence of distant metastases from intrahepatic cholangiocarcinoma is about 40% [4]. Due to its low prevalence, there are few large-scale studies for clinical guidance and management of patients with ICC.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the above studies are based on molecular and cellular level research and are di cult to apply to clinical decision-making. Previous research revealed that risk factors for ICC patients with metastasis include T-stage, tumor size, age, pathological grade, and lymph node metastasis [4]. In terms of gender, there are more male patients than female patients [13], and the median age of ICCA patients at diagnosis was over 65 years [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 Patients with iCCA have a worse prognosis than those with eCCA, with lower rates of overall survival (OS) and cancer-specific survival. 12 …”
Section: Introductionmentioning
confidence: 99%